2005
DOI: 10.1111/j.1744-6570.2005.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Conscientiousness: An Empirical Investigation Based on Seven Major Personality Questionnaires

Abstract: The purpose of this study was to identify the underlying structure of the trait domain of Conscientiousness using scales drawn from 7 major personality inventories. Thirty-six scales conceptually related to Conscientiousness were administered to a large community sample (N = 737); analyses of those scales revealed a hierarchical structure with 6 factors: industriousness, order, self-control, responsibility, traditionalism, and virtue. All 6 factors demonstrated excellent convergent validity. Three of the 6 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
622
3
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 639 publications
(661 citation statements)
references
References 102 publications
30
622
3
6
Order By: Relevance
“…Roberts et al (2005a) described these facets: Order deals with the ability to organise and plan tasks and activities (example item: I need a neat environment in order to work well). Virtue reflects adherence to moral standards, honesty, and "good Samaritan" behaviour (example item: If I find money laying around, I"ll keep it to myself).…”
Section: Measures and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Roberts et al (2005a) described these facets: Order deals with the ability to organise and plan tasks and activities (example item: I need a neat environment in order to work well). Virtue reflects adherence to moral standards, honesty, and "good Samaritan" behaviour (example item: If I find money laying around, I"ll keep it to myself).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Research into the factor structure of C provides evidence for six lower order facets: Order, Virtue, Traditionalism, Self-control, Responsibility, and Industriousness (Roberts, Chernyshenko, Stark, & Goldberg, 2005a). The latest work has emphasised the importance of examining facet effects in the study of C (see Roberts, Lejuez, Krueger, Richards & Hill, in press).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have distinguished empirically and conceptually between two sub-factors of Conscientiousness -active industriousness sometimes referred to as Achievement Orientation, and diligent, rule-following Dependability with its emphasis on orderly, hard-working reliability (e.g., Roberts, Chernyshenko, Stark, & Goldberg, 2005). Similarly, distinguishable facets of Extraversion have been identified as Affiliation (strongly desiring social interaction) and Social Potency (proactivity in influencing other people) (e.g., DeYoung, Quilty, & Peterson, 2007).…”
Section: ---------------------------mentioning
confidence: 99%
“…Because self-control is considered to be a lower-order facet of conscientiousness (Roberts, Chernyshenko, Stark, & Goldberg, 2005) and is an established predictor of unemployment (Daly, Delaney, Egan, & Baumeister, 2015), we tested whether conscientiousness was associated with unemployment independently of the effects of self-control. That robustness test found that controlling for childhood self-control reduced the conscientiousness coefficient slightly without altering its significance level (see Table S1).…”
mentioning
confidence: 99%